GURU DAN ORANG TUA DALAM PENCAPAIAN PRESTASI ANAK TUNAGRAHITA DI SLB NEGERI PEMBINA PEKANBARU - Juliani "; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Child is the most beautiful gift given by Allah. But sometimes some children look different from most children, such as those with mental disabilities. Tunagrahita is a mental disorder  that occurs in someone who has an IQ below the average. Some mentally retartded children have the opportunity to get the same education and achievement as children in general. One of them is in the new supervisory state Sekolah Luar Biasa Negeri Pembina Pekanbaru. In this case the teacher and the parents are very instrumental in supporting a success and development that occurs to them as well as achieving an achievement and the sosialization that is held. Then this study aims to find out how much cooperation teachers and parents have in improving a achievement of tunagrahita children in foreign Sekolah Luar Biasa Negeri Pembina Pekanbaru. The research method used is a quqlitative method. The theory in this study consists of McClland’s theory of needs and Mead’s self development sosialization. In this study the number of informants was 5 people. Data collection techniques by means of interviews, observation, and documentation. The results of this study are to see the success of teachers and parents in achiving achievements of tunagrahita children and can be seen by the public that children who have limitations also have more achievements to pround of like children in general.Keywords:  Teachers, parents, achievements, tuagrahita children, socialization